ssDNA-dependent colocalization of adeno-associated virus Rep and herpes simplex virus ICP8 in nuclear replication domains - Heilbronn, Regine (Oxford University Press, 2003)
The subnuclear distribution of replication complex proteins is being recognized as an important factor for the control of DNA replication. Herpes simplex virus (HSV) single-strand (ss)DNA-binding protein, ICP8 (infected cell protein 8) accumulates in nuclear replication domains. ICP8 also serves as helper function for the replication of adeno-associated virus (AAV). Using quantitative 3D colocalization analysis we show that upon coinfection of AAV and HSV the AAV replication protein Rep and ICP8 co-reside in HSV replication domains. In contrast, Rep expressed by a recombinant HSV, in the absence of AAV DNA, displayed a nuclear distribution pattern distinct from that of ICP8. Colocal ization of Rep and ICP8 was restored by the reintroduction of single-stranded AAV vector genomes. In vitro, ICP8 displayed direct binding to Rep78. Single-stranded recombinant AAV DNA strongly stimulated this interaction, whereas double-stranded DNA was ineffective. Our findings suggest that ICP8 by its strong ssDNA-binding activity exploits the unique single-strandedness of the AAV genome to form a tripartite complex with Rep78 and AAV ssDNA. This novel mechanism for recruiting components of a functional replication complex directs AAV to subnuclear HSV replication compartments where the HSV replication complex can replicate the AAV genome.